The Role of Green Marketing and Promotion of Green Energy Bonds to Reduce Carbon Emissions in Indonesia - Sabbar, Sabbar Dahham; Musa, Hani Amer; Kadir, Abdul Rahman; Nohong, Mursalim; Manan, Arifuddin; Munizu, Musran; Anwar, Anas Iswanto (International Journal of Energy Economics and Policy, 2023)
This paper investigates the impact of green marketing on the adoption of green bonds. Using econometric methods, the study uses panel data of Indonesia 560 Indonesian firms regulated under the Indonesia Stock Market from 2002 to 2021. The findings show that green marketing can increase the demand for green bonds. This is because green marketing can raise awareness of the benefits of green bonds and can make them more attractive to investors. The study also finds that income and trade openness positively correlate with carbon dioxide emissions, while human capital is negatively correlated with carbon dioxide emissions. This suggests that countries with higher incomes and more trade openness tend to emit more carbon dioxide. In contrast, countries with higher levels of human capital tend to emit less carbon dioxide. Overall, the study’s findings offer important new information about how green marketing affects the adoption of green bonds and the connection between economic variables and carbon dioxide emissions. The findings could encourage the use of green bonds and lower carbon dioxide emissions. They also have ramifications for investors and governments.